જો $x > 2$ માટે $f(x) = \frac{1}{{\sqrt {x + 2\sqrt {2x - 4} } }} + \frac{1}{{\sqrt {x - 2\sqrt {2x - 4} } }}$ ,તો $f(11) = $
$7/6$
$5/6$
$6/7$
$5/7$
વિધેય $f(x) = \frac{{\sqrt {1 - {x^2}} }}{{1 + \left| x \right|}}$ નો વિસ્તાર ......... છે.
અહી $[x]$ એ મહતમ પૃણાંક વિધેય છે. જો વાસ્તવિક વિધેય $\mathrm{f}(\mathrm{x})=\sqrt{\frac{[\mathrm{x}] \mid-2}{\sqrt{[\mathrm{x}] \mid-3}}}$ નો પ્રદેશ $(-\infty, \mathrm{a}) \cup[\mathrm{b}, \mathrm{c}) \cup[4, \infty), \mathrm{a}\,<\,\mathrm{b}\,<\,\mathrm{c}$, હોય તો $\mathrm{a}+\mathrm{b}+\mathrm{c}$ ની કિમંત મેળવો.
વિધેય $f(x)={\left( {1 + \frac{1}{x}} \right)^x}$ હોય તો $f (x)$ નો પ્રદેશ મેળવો.
જો દરેક $x,\;y \in R$ માટે $f:R \to R$ ;$f(x + y) = f(x) + f(y)$ નું પાલન કરે છે અને $f(1) = 7$ તો $\sum\limits_{r = 1}^n {f(r)} =$
ધારો કે $a,b,c\; \in R.$ જો $f\left( x \right) = a{x^2} + bx + c$ હોય કે જેથી $a + b + c = 3$ અને $f\left( {x + y} \right) = f\left( x \right) + f\left( y \right) + xy,$ $\forall x,y \in R,$ તો $\mathop \sum \limits_{n = 1}^{10} f\left( n \right)$ની કિંમત મેળવો.